Concise Portraits: Roland Barthes, ‘Masculine, Feminine, Neuter’ and Other Writings on Literature: Essays and Interviews, Volume 3, trans. by Chris Turner and Roland Barthes, ‘Simply a Particular Contemporary’: Interviews, 1970-79: Essays and Interviews, Volume 5, trans. by Chris Turner - Ferguson, S (Cardiff University, 2017)
The completion of Seagull Books' five volumes of translations by Chris Turner in the milestone in the publication of Barthes's works in English, as now almost the whole contents of the Éditions du Seuil's Oeuvres completés are available in translation. The only substantial area of Barthes' work that is not yet fully accessible to an Anglophone readership is his teaching in seminars and lectures, and this editorial process is not yet completed in French either. As Chris Turner acknowledged in an interview for Barthes Studies (1 (2015) 158-64), this editorial tidying up has led to an eclectic group of texts and a somewhat division between the different volumes. Nonetheless, the two volumes reviewed here - featuring critical writing on literature and a selection of interviews respectively - not only present some valuable texts translated in a proficiant and appropriate manner, but also possess a meaningful coherence of their own.